Antioxidants in Cocoa - Żyżelewicz, Dorota; Oracz, Joanna (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue comprises articles related to the effects of genotype and processing conditions on the phenolic compound profile and antioxidant activity of cocoa-derived products, isolation and characterization of antioxidant compounds such as polyphenols and melanoidins from cocoa beans, and assessment of the antioxidant, antioxidative stress and anti-inflammatory effects of cocoa beans and cocoa-derived products. The results of these studies show that it is possible to maintain or increase the biological activity of cocoa beans and their derived products (cocoa powder and chocolate) by choosing appropriate processing conditions and cocoa genotype and origin. The papers published in this Special Issue confirm that cocoa beans and cocoa by-products can be considered as an attractive source material for manufacturing of functional foods and nutraceuticals. This is because they contain many bioactive compounds, mainly polyphenols, including flavonoids (proanthocyaninidins, monomeric flavan-3-ols, and anthocyanins) and phenolic acids, as well as melanoidins. Finally, the in vitro and in vivo studies demonstrate the importance of cocoa antioxidants for the prevention of oxidative stress and inflammation.